MODEL PENGEMBANGAN KEWIRAUSAHAAN DI PERGURUAN TINGGI ENTREPRENEURSHIP DEVELOPMENT MODEL IN HIGHER EDUCATION - Anis Marjukah; Arif Julianto Sri Nugroho; Nursito, sarwono (Widya Dharma Journal of Business - WIJoB, 2024)
Higher education plays an important role in driving change towards global competitiveness by providing motivation and producing graduates to become entrepreneurs. Increasing the number of entrepreneurs is expected to create jobs and reduce unemployment. This study aims to find a model for developing entrepreneurship among academics. The type of research is descriptive qualitative. The purposive sampling technique was used as a sampling technique for the study, with the number of samples is 20 informants who had participated in the entrepreneurship development program, using a questionnaire. The results of the study showed that: students generally have a positive perception of entrepreneurship, with a high interest in entrepreneurship, and have sufficient potential to become new entrepreneurs. However, there are still limitations, including limited capital, the ability to read business opportunities and the courage to start a business.